Pengaruh Gerakan Nasional Non Tunai, Social Influence, Dan Persepsi Kemudahan Penggunaan Terhadap Minat Menggunakan Digital Payment Dalam Konsep Maslahah (Studi Kasus : Kota Kisaran) - Kartika, Anggi; Nurbaiti, Nurbaiti; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine the influence of the National Non-Cash Movement, Social Influence and Perceived Ease of Use on Interests in Using Digital Payments in the Concept of Maslahah in Kisaran City Communities, both partially and simultaneously. This research uses quantitative research methods. The population in this study is the people of Kota Kisaran. The sampling technique used was non-probability sampling, namely purposive sampling with a total sample of 100 respondents. Data collection techniques using a questionnaire. The primary data obtained was analyzed through the IBM SPSS statistics 25 program. The results showed that first, the National Non-Cash Movement had a positive and significant effect on Digital Payments for the Kisaran City Community with a significant value of 0.006 <0.05. Second, Social Influence has a positive and significant effect on Digital Payments for Kisaran City Communities with a significant value of 0.000 <0.05. The three Perceived Ease of Use have a positive and significant effect on Digital Payments in Kisaran City Communities with a significant value of 0.000 <0.05. Fourth, simultaneously the Non-Cash National Movement, Social Influence and Perception of Ease of Use have a positive and significant effect on Digital Payment with a significant value of 0.000 <0.05.